Strengthening Digital Learning for Archipelago Teachers in Letti Island: Pengabdian - Meyer, Fredi; Tiwery, Yulina; Sarah Kamanasa, Louisa; Sartin Tiwery, Dian; Saartje Ferdinandus, Marcy; F. J. Lekawael, Rosina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program titled